(3OdGdI GdHUeI GdhQGKjI hOhQgG aj GdEKHGJ GdLfGFj (B:s (3OQGSI JMdjdjI hJCUjdjI ebGQfI (B/s - (3GdTeQj, YhGO jhSa MSjfs ((3GdLjRI, LeghQjI eUQ GdYQHjI (B:s (3eQcR GdOQGSGJ GdYQHjI ddfTQ hGdJhRjY,s, 2018)
(3jJfGhd gPG GdcJGH GdHMK aj HGHjf JSHbgeG ebOeI haUd JegjOj hOGQJ ehVhYGJg Mhd (B((3eQGMd GdJWhQ GdJGQjNj dhSGFd GdEKHGJ GdLfGFj hGdLGfH GdYdej ddHUeI GdhQGKjI hMLjJgG heLGdGJ GSJNOGe GdHUeI GdhQGKjI(B) (3jJJHY CgejI gPG GdcJGH ef CgejI GdHUeI GdhQGKjI EP JYO gPg GdhSjdI ef GdbQGFf GdYdejI GdeSJMOKI GdJj dgG bjeI HQgGfjI aj GdEKHGJ hPdc WHbG deLGd GSJNOGegG hWHjYJg habG ddXQha hGdedGHSGJ GdeMjWI HGdLQjeI(B. s
(3GdeMJhjGJ (B: (3GdebOeI(B-(3GdaUd GdJegjOj (B: (3eQGMd GdJWhQ GdJGQjNj dhSGFd GdEKHGJ GdLfGFj(B-(3GdHGH GdChd (B: (3GdLGfH GdYedj ddHUeI GdhQGKjI hMLjJgG aj Gdabg GdESdGej hGdbGfhf GdhVYj, GdaUd GdChd (B: (3GdJbfjI GdYdejI ddHUeI GdhQGKjI(B-(3GdaUd GdKGfj (B: (3MLjI GdHUeI GdhQGKjI aj Gdabg GdESdGej hGdbGfhf GdhVYj(B-(3GdHGH GdKGfj (B: (3eLGdGJ GSJNOGe GdHUeI GdhQGKjI, GdaUd GdChd (B: (3GSJNOGe GdHUeI GdhQGKjI aj eLGd GdEKHGJ GdLfGFj(B-(3GdaUd GdKGfj (B: (3GSJNOGe GdHUeI GdhQGbjI aj eLGd EKHGJ GdfSH hfajg(B-(3GdNGJeI(B-(3GdeUGOQ hGdeQGLY(B. s
(3HHdjhLQGajI (B: (3UaMI (B337-362.s
Keywords: (3GdEKHGJ GdLfGFjs; (3GdCOdI GdLfGFjIs; (3GdHUeI GdhQGKjIs -- (3bhGfjf hJTQjYGJs; (3GdgfOSI GdhQGKjIs -- (3bhGfjf hJTQjYGJs